Association between continuity of care (COC), healthcare use and costs: what can we learn from claims data? A rapid review - Anna Nicolet; Muaamar Al-Gobari; Clémence Perraudin; Joël Wagner; Isabelle Peytremann-Bridevaux; Joachim Marti (BMC, 2022)
Abstract Objective To describe how longitudinal continuity of care (COC) is measured using claims-based data and to review its association with healthcare use and costs. Research design Rapid review of the literature. Methods We searched Medline (PubMed), EMBASE and Cochrane Central, manually checked the references of included studies, and hand-searched websites for potentially additional eligible studies. Results We included 46 studies conducted in North America, East Asia and Europe, which used 14 COC indicators. Most reported studies (39/46) showed that higher COC was associated with lower healthcare use and costs. Most studies (37/46) adjusted for possible time bias and discussed causality between the outcomes and COC, or at least acknowledged the lack of it as a limitation. Conclusions Whereas a wide range of indicators is used to measure COC in claims-based data, associations between COC and healthcare use and costs were consistent, showing lower healthcare use and costs with higher COC. Results were observed in various population groups from multiple countries and settings. Further research is needed to make stronger causal claims.